Catching the Butterfly and the Homunculus of n Carinae with ALMA - Zapata, Luis A. (2022)
The nature and origin of the molecular gas component located in the circumstellar vicinity of n Carinae are still far from being completely understood. Here, we present Atacama Large Millimeter/submillimeter Array CO(3-2) observations with a high angular resolution (∼0.″15) and a great sensitivity that are employed to reveal the origin of this component in n Carinae. These observations reveal much higher velocity (-300 to +270 km s-1) blue- and redshifted molecular thermal emission than previously reported, which we associate with the lobes of the Homunculus Nebula, and which delineates very well the innermost contours of the red- and blueshifted lobes likely due to limb brightening. The inner contour of the redshifted emission was proposed to be a disrupted torus, but here we reveal that it is at least part of the molecular emission originating from the lobes and/or the expanding equatorial skirt. On the other hand, closer to systemic velocities (±100 km s-1), the CO molecular gas traces an inner butterfly-shaped structure that is also revealed at near-IR and mid-IR wavelengths as the region in which the shielded dust resides. The location and kinematics of the molecular component indicate that this material has formed after the different eruptions of n Carinae.